Beef production as influenced by stage of maturity of grass for silage and level and type of supplementary concentrates - Aronen, Ilmo; Toivonen, Vesa; Ketoja, Elise; Öfversten, Jukka (Agricultural Research Centre of Finland, The Scientific Agricultural Society of Finland, The Finnish Society of Dairy Science, 1992)
Tutkimuksessa selvitettiin, miten säilörehun korjuuaste (aikaisin (=EC) tai 8 päivää myöhemmin (=LC) korjattu koiranheinä-timoteisäilörehu), väkirehutäydennyksen määrä (matala (=LL, 1.5 kg kuiva-ainetta (ka)/pv) tai korkea (=HL, 3.0 kg ka/pv) ja laatu (väkirehuna ohra (=B) tai ohran ja rypsirouheen seos (=BRSM)vaikuttavat rehuannoksen sulavuuteen sekä ay-sonnien säilörehun syöntiin ja kasvunopeuteen. Tutkimuksessa käytettiin satunnaistettujen lohkojen koekaaviota ja 23 faktoriaalisia koetekijöitä. Vapaasti syötettyjen EC ja LC säilörehujen raakavalkuaispitoisuudet olivat keskimäärin 15.9 ja 13.1 %. Vastaavat raakakuitupitoisuudet olivat 27.8 ja 30.4 %. Tutkimuksen alussa EC sonnit söivät enemmän säilörehua kuin LC sonnit. Ero kuitenkin pieneni kokeen edetessä. Eläinten kasvu seurasi säilörehun syöntiä siten, että kasvatuskauden alun LC sonnien hitaampi kasvunopeus kompensoitui kokeen edetessä. HL sonnit söivät vähemmän säilörehua kuin LL sonnit. Kasvuasteesta riippumatta säilörehun kuiva-aineen syönti väheni keskimäärin 0.63 kg lisättyä väkirehun kuiva-ainekiloa kohti. Aikaisin korjattua säilörehua ja ohraa syötettäessä rehuannoksen laskennallinen valkuaisväkevyys suomalaisten normien mukaan oli riittävä. Kuitenkin rypsirouheen sisällyttäminen rehuannokseen (500 g koko kasvatuskauden ajan) lisäsi eläinten säilörehun syöntiä kasvuasteesta riippumatta. Myös sonnien kasvu nopeutui merkitsevästi ja rehun hyväksikäyttö oli tehokkaampaa BRSM ruokinnalla B ruokintaan verrattuna. Näin ollen on ilmeistä, että sonnit eivät pystyneet käyttämään hyväkseen kaikkea aikaisin korjatun säilörehun typpeä. Rypsirouheen säilörehun syöntiä lisäävä vaikutus viittaa siihen, että nimenomaan pötsimikrobit hyötyivät rypsirouheen valkuaisesta. Tätä päätelmää tukee tutkimuksessa havaittu, rypsirouheen rehuannoksen sulavuutta lisäävä vaikutus. On myös mahdollista, että rypsirouheen pötsissä hajoamaton ohitusvalkuainen vaikutti myönteisesti eläinten kasvuun.

The aim of this study was to examine the effects of stage of maturity of grass for silage (EC = early cut, LC = late cut), and level (LL = low level, i.e., 1.5 kg dry matter (DM) d-1, HL = high level, i.e., 3.0 kg DM d-1) and type (B = barley, BRSM = barley and heatmoisture treated rapeseed meal) of supplementary concentrates on feed intake, animal performance and diet digestion in Finnish Ayrshire bulls. The study was conducted as a 23 factorial experiment with six randomized complete blocks. The average initial and final live weights of the bulls were 123 kg and 494 kg, respectively. The crude protein content of the ad libitum fed EC and LC silages, cut at an interval of eight days, was 159 and 131 g kg-1 DM. However, the difference in the estimated content of AAT (= amino acids absorbed in the small intestine) between the two silages was small, whereas there was a large difference in PBV (= protein balance in the rumen). The respective values for crude fibre were 278 and 304 g kg-1 DM. At the beginning of the experiment the voluntary grass silage intake of the EC bulls was higher than that of the LC bulls. Towards the end of the experiment the difference in silage intake between the two stages of cut disappeared. This change in voluntary grass silage intake was followed by a similar change in the rate of dally live weight gain (LWG): the EC bulls started to grow faster than the LC bulls, but the initial slower LWG of the LC bulls had been compensated by the end of the experiment. The LL bulls had a higher intake of silage than the HL bulls. The substitution rate was 0.63 kg silage DM per concentrate DM, regardless of the stage of cut. HL feeding resulted in faster LWG. Owing, at least partly, to the improved diet digestibility, inclusion of rapeseed meal in the diet increased the silage intake throughout the experiment followed by a faster LWG. The positive effect of rapeseed meal was unaffected by the stage of maturity of the grass for silage and the level of concentrate supply. The animals were not able to take full advantage of the high protein content of the EC silage. The inclusion of rapeseed meal in the diet, however, improved the rate of gain and resulted in more efficient feed conversion.
Keywords: säilörehu; rapeseed meal; protein evaluation; diet digestion; feed intake; substitution rate; live weight gain